Comparison of the Effectiveness of Radiofrequency Ablation Aortorenal Ganglia in Patients with Hypertension, Depending on the State of the Autonomic Nervous System - B. V. Batsak; B. N. Gumenyuk; E. M. Trembovetskaya; V. V. Lazorishinetz (Ukrainian Journal of Cardiovascular Surgery, 2016)
The aim of this study was to explore the efficacy of radiofrequency ablation of renal paravertebral sympathetic ganglia to reduce blood pressure in patients with essential hypertension in hypertensive patients, depending on the state of the autonomic nervous system.36 patients with arterial hypertension underwent radiofrequency ablation of prevertebral sympathetic ganglia. The hypersympathetic state was in 24 patients.It was found more significant reduction in systolic blood pressure (in the group average of 29,3±7,5 mm Hg) in patients with hypersympathetic state compared with patients without hypersympathetic state respectively 15,3±4,5 mm Hg, 12 months after ablation.Our result indicate that the radiofrequency ablation of the sympathetic preverberal ganglia significantly lowering blood pressure in patients with chronic activation of sympathetic nervous system.